PEMANFAATAN SIMULASI PHET DALAM MENDUKUNG PEMBELAJARAN FISIKA MATERI RANGKAIAN LISTRIK SEARAH PADA MASA PANDEMI - Umam, Ahmad Khotibul; Haryadi, Rudi (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2021)
The purpose of this study was to determine the use of PhET simulation in physics learning on electric circuit material during the pandemic. The research method used is descriptive qualitative research with literature studies from various articles. The results showed that the PhET simulation was very effective to be applied in supporting the physics learning of unidirectional electric circuits during the pandemic. This is shown by the data on the presentation of learning outcomes after using the PhET simulation where the average results have increased. In addition, from the misconception side, it has also changed for the better. There are fewer students who have misconceptions.